2021
DOI: 10.5650/jos.ess20198
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluation of the Excessive Intake of Ceramide-Containing Acetic Acid Bacteria - A Randomized, Double-Blind, Placebo-Controlled Study Over a 4-week Period

Abstract: decrease in the stratum corneum of aged skin 2 .Supplementing ceramide to the skin contributes in maintaining or improving the skin barrier function. It has been reported that the application of ceramide-containing cream improved the destruction of the skin barrier, induced by tape stripping or sodium lauryl sulfate treatment 4 . Oral intake of plant-derived ceramides has also been reported to reduce transepidermal water loss TEWL in mice 5,6 , in healthy adults 6 , and even in patients with atopic dermatitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Orally administered plant glucosylceramides (GlcCERs) derived from rice and konjac can elevate epidermis CERs by mechanisms including direct localization and usage of absorbed diet CERs in the epidermis without any metabolism conversion, the usage of exogenetic GlcCERs metabolins by keratinocytes to establish their own sphingolipids or the generation of skin CERs by metabolins ( 98 ). Other proposed mechanisms regarding skin barrier improvement include the stimulation of collagen synthesis ( 40 ), the inhibition of matrix proteases ( 40 ), and the elevation of the expression of aquaporin-3 ( 46 ). The improvement in skin moisture content resulting from the oral intake of ceramides is likely to be induced by the combination of the mechanisms described above.…”
Section: Discussionmentioning
confidence: 99%
“…Orally administered plant glucosylceramides (GlcCERs) derived from rice and konjac can elevate epidermis CERs by mechanisms including direct localization and usage of absorbed diet CERs in the epidermis without any metabolism conversion, the usage of exogenetic GlcCERs metabolins by keratinocytes to establish their own sphingolipids or the generation of skin CERs by metabolins ( 98 ). Other proposed mechanisms regarding skin barrier improvement include the stimulation of collagen synthesis ( 40 ), the inhibition of matrix proteases ( 40 ), and the elevation of the expression of aquaporin-3 ( 46 ). The improvement in skin moisture content resulting from the oral intake of ceramides is likely to be induced by the combination of the mechanisms described above.…”
Section: Discussionmentioning
confidence: 99%
“…A group of 30 healthy adults (including women and men) aged 20 to 60 years old were selected and they consumed dietary supplements (including 1197 mg of acetic acid bacteria containing 9.06 mg of ceramide) for four consecutive weeks. Physical measurements, blood tests, and urine analyses showed that ceramide can preserve the skin barrier [ 43 ]. This reveals that ceramide has a role in protecting the skin and resisting the influence of external substances on skin aging.…”
Section: Research On Skin Anti-aging Compoundsmentioning
confidence: 99%
“…The impact of orally administered SCFAs on neurologic injury outcomes is still being investigated and has not been adequately tested on human neurologic injury patients in a clinical setting. However, SCFAs appear to have a relatively safe profile and can be administered easily through oral intake [ 118 ]. Thus, although more research is needed to evaluate efficacy in human subjects in this context, oral SCFAs may eventually serve as a safe and easy-to-use adjunct to post-neurologic injury therapy to improve patient outcomes.…”
Section: Interventionsmentioning
confidence: 99%